2016
DOI: 10.1177/1357633x15625400
|View full text |Cite
|
Sign up to set email alerts
|

Comparing smartphone camera adapters in imaging post-operative cataract patients

Abstract: Introduction The goal of this study is to compare image quality and clinical confidence for managing post-operative cataract patients based on anterior segment smartphone images obtained in real-world settings using four types of adapters: (a) macro lens (ML), (b) ML with augmented light-emitting diode (LED) illumination (ML-LED), (c) no adapter (NA) and (d) slit lamp (SL) adapter. Methods Anterior segment images were obtained from 190 eyes after cataract surgery using an eight-megapixel iPhone 6 smartphone ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Evidence on e-health technologies on cataract and age-related macular degeneration screening is still poor and on small populations, even the modest literature on these topics has shown an overall good quality of acquired images in 93-100% of cases [ 27 ].…”
Section: Diabetic Retinopathy Management During Covid-19mentioning
confidence: 99%
“…Evidence on e-health technologies on cataract and age-related macular degeneration screening is still poor and on small populations, even the modest literature on these topics has shown an overall good quality of acquired images in 93-100% of cases [ 27 ].…”
Section: Diabetic Retinopathy Management During Covid-19mentioning
confidence: 99%
“…Ophthalmologists can sometimes benefit from a mobile phone photo of the eye when triaging remotely patients’ complaints. A mobile phone camera with proper focus and flash illumination can generate a clinically useful image in postop cataract patients [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the efficacy of smartphone-based slit-lamp devices. Moreover, several studies have indicated that an external convex lens enables adjustment of the magnification to the eyes [23,24]. Recently, Hu S, et al demonstrated the efficiency of smartphone-based slit-lamps for cataract screening.…”
Section: Discussionmentioning
confidence: 99%